Branch Campuses Weigh Start-up Options - Stanfield, David (International Higher Education, 2013)
With over 200 international branch campuses now in operation, new entrants can benefit from previous experience to guide start-up decisions. Thoughtful strategic decisions in three categories–first-mover vs. established market, comprehensive vs. narrow focus, and collaborative vs. autonomous–will likely contribute to their success.